2010
DOI: 10.1007/s10528-010-9348-x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Heterologous Expression, and Functional Characterization of a Chitinase Gene, Lbchi32, from Limonium bicolor

Abstract: In the present study, an endochitinase gene, Lbchi32, was cloned from Limonium bicolor. The cDNA sequence of Lbchi32 was 1,443 bp in length and encoded 319 amino acid residues. The DNA sequence of Lbchi32 was 2,512 bp in length and contained three exons and two introns. The Lbchi32 gene was inserted into a pPIC9 vector and transferred into Pichia pastoris strains GS115 and KM71 for heterologous expression. SDS-PAGE analyses indicated that LbCHI32 was expressed in both GS115 and KM71 and that it was secreted ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Five out of the 15 enriched GO terms in Triticeae can be related to resistance to fungal pathogens via three different mechanisms. Chitinases are enzymes, which are known to be involved in plants' fungal resistance and have been extensively studied in wheat species [28,29]. The ability of these enzymes to degrade chitin, a primary component of fungal cell walls, can lead to the lysis of fungal cells and therefore provide resistance against them.…”
Section: Resistance To Fungi In Wheatmentioning
confidence: 99%
“…Five out of the 15 enriched GO terms in Triticeae can be related to resistance to fungal pathogens via three different mechanisms. Chitinases are enzymes, which are known to be involved in plants' fungal resistance and have been extensively studied in wheat species [28,29]. The ability of these enzymes to degrade chitin, a primary component of fungal cell walls, can lead to the lysis of fungal cells and therefore provide resistance against them.…”
Section: Resistance To Fungi In Wheatmentioning
confidence: 99%
“…Though many mutants in salt secretion have been obtained using gamma ray irradiation ( Yuan et al, 2013 ), no recretohalophyte where specific genes have been silenced has been developed. Until now, the experiments suggesting candidate genes have only been reported in heterologous expression, such as Lbchi32 of L. bicolor verified in pathogenic fungi ( Liu et al, 2010 ). So the mutants in specific and candidate genes should be investigated in the future in order to accurately study molecular mechanism of salt secretion.…”
Section: A Possible Pathway For Secreting Salt From the Salt Glandmentioning
confidence: 99%
“…The activities of four different recombinant chitinases, inrCHI31, exrCHI31, inrCHI32, and exrCHI32, towards different substrates were measured using Schales method [15]. While four recombinant chitinases demonstrated activity as a response to all test substrates, analysis of variance showed that their decomposing activities towards different substrates were significantly different ( P < 0.05) (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…The optimal temperature and pH for chitinase activity, thermal stability, and the effects of ions on enzyme activity, and the rate of decomposition of fungal cell walls of recombinant chitinases inrCHI31, exrCHI31, inrCHI32, and exrCHI32 were investigated according to the technique described by Liu et al [14, 15]. …”
Section: Methodsmentioning
confidence: 99%